2013
DOI: 10.15288/jsad.2013.74.136
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Morbidity is Linked to Problem Drinking in Midlife Among Alcohol-Dependent Men: A Co-Twin Control Study

Abstract: ABSTRACT. Objective: Prior research on predictors of problem drinking has been limited because of an inability to attribute an unambiguous environmental explanation to observed fi ndings. Using a prospective co-twin control design, we examined the extent to which a history of psychiatric symptoms exerts an environmental infl uence on problem drinking in midlife that is unconfounded by genetic underpinnings. Method: Participants were 367 complete male twin pairs (208 monozygotic, 159 dizygotic) from the Vietnam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The clinical subpopulation with a dual diagnosis of AUD and a psychiatric problem should be studied in greater detail, because such dual diagnoses have been shown to be associated with a poorer prognosis for both conditions [14, 33, 34, 44]. …”
Section: Discussionmentioning
confidence: 99%
“…The clinical subpopulation with a dual diagnosis of AUD and a psychiatric problem should be studied in greater detail, because such dual diagnoses have been shown to be associated with a poorer prognosis for both conditions [14, 33, 34, 44]. …”
Section: Discussionmentioning
confidence: 99%
“…These findings build upon prior work showing variability in AUD course during midlife 1,2 and an environmental link between psychiatric morbidity and problem drinking in midlife. 7 Collectively, these studies address two broad factors theorized to impact AUD course over the lifespan, 5 and represent-to our knowledge-the only discordant-twin studies to test whether these factors differentiate course of problem drinking in midlife. Given the complexity of the issue, the findings of discordant-twin studies alone cannot unequivocally demonstrate a nongenetic interpretation in observed associations.…”
Section: Discussionmentioning
confidence: 99%
“…The conceptual framework of Moos and colleagues outlines two broad domains that influence the course of drinking over the lifespan: (1) personal characteristics/functioning and (2) socio‐contextual factors. In a prior discordant‐twin study, we targeted the former domain and found that among twins from the Vietnam‐Era Twin Registry (VETR) who were concordant for AUD history, differences in psychiatric symptoms during midlife were associated with differences in problem drinking over this timeframe . Discordant‐twin designs have not been used to test whether socio‐contextual factors differentiate the course of AUD in midlife.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Schuckit et al (1995) reported that after controlling for substanceinduced "organic" anxiety syndromes and controlling for assortative mating in the parents of probands, there was no evidence of an exceptionally high rate of anxiety disorders in the close relatives of alcoholic men and women. Similarly, Blonigen et al (2013) found that the within-twin-pair differences in lifetime internalizing disorders (comprised of common affective and anxiety disorders) were signifi cantly related to the within-twin-pair differences in the development of alcohol problems 10 years later (i.e., the twin with the earlier internalizing disorder had more risk for the development of later alcohol problems). They concluded that a history of such psychiatric problems "appears to be linked to problem drinking in midlife above and beyond the confounding infl uence of genetic effects" (p. 136).…”
Section: Modern Family Studies Of Comorbiditymentioning
confidence: 91%